Experıences of loss and theır management by ınformal caregıvers ın the communıty. Perceıved Qualıty of Lıfe of people wıth chronıc dıseases - Tsaga, Helen; Argyriadi, Agathi; Argyriadis, Alexandros (Health & Research Journal, 2024)
Background: Informal caregivers play a vital role in caring for patients with chronic illnesses, but this care can significantly affect their mental health and well-being, particularly after the loss of the patient. Due to the significance of the issue and limited research in the field, it is important to identify factors associated with the mental health of informal caregivers. Method and Material: This study aimed to investigate the experiences of loss and their management by informal caregivers of people with chronic diseases. Specifically, it evaluated the relationship between experiences of loss and (1) mental health and (2) socio-demographic characteristics of informal caregivers. A quantitative survey was conducted on a sample of 98 informal caregivers of patients with chronic diseases, using the Core Bereavement scales BEQ-24 and DASS-21. Results: The data analysis revealed that 25.5% of informal caregivers were prepared to experience loss, while only 12.2% sought psychological support to manage their experiences. Informal caregivers often experienced loss with sadness, loneliness, and nostalgia while recalling memories with the deceased patient. Fewer caregivers experienced guilt, self-blame, and anger or sought to fulfill their emotional and existential needs. The study also found that experiences of loss were associated with symptoms of depression, anxiety, and stress in informal caregivers of people with chronic diseases. Conclusions: The study underscores the impact of caring for patients with chronic illnesses on mental health and wellbeing of informal caregivers, particularly after the loss of the patient. The results highlight the need for interventions to support informal caregivers.